THE CONTRIBUTION OF MINAHASA WOMEN IN SOCIAL, POLITICAL, AND EDUCATIONAL CONSTRUCTION “A Socio-Historical Study on the Role of Maria Walanda Maramis” - Gelar, Wolter Weol; Sumendap, Ryanto; Kaunang, Ivan Robert Bernadus; Wangkai, Rut Ketsia (Advances In Social Humanities Research, 2025)
asbtract